Nanofibrous alumina structures fabricated using high-yield alternating current electrospinning. Issue 15 (15th November 2016) - Stanishevsky, Andrei; Brayer, W. Anthony; Pokorny, Pavel; Kalous, Tomáš; Lukáš, David
Abstract: Nanofibrous alumina (Al2 O3 ) structures were fabricated from the precursor aluminum nitrate/polyvinylpyrrolidone (PVP) nanofibers prepared using a free-surface alternating current (AC) electrospinning method. Precursor nanofibers were generated at rates up to 6.4 g/h and collected as 100–300 µm thick sheets suitable for direct conversion into the nanofibrous alumina structures. The effects of process conditions and annealing temperature on the nanofiber diameter, morphology, shrinking behavior and crystalline phase formation were investigated by Scanning Electron Microscopy (SEM), Fourier Transform Infrared (FTIR) spectroscopy, and X-ray diffraction (XRD). Textural properties of Al2 O3 fibrous sheets composed of micro-/meso-porous nanocrystalline γ-alumina nanofibers with 260±90 nm diameters after the calcination at temperatures in the range from 700 °C to 1000 °C were determined from N2 adsorption/desorption isotherms. Preliminary air permeability and apparent air flow resistance studies of single sheet and multilayer nanofibrous alumina membranes were performed and compared with other porous alumina membrane structures for the evaluation of their possible usage in gas filtration, separation, and other applications.